Antimicrobial Peptides: A Promising Solution to the Rising Threat of Antibiotic Resistance - Tarequl Islam; Noshin Tabassum Tamanna; Md Shahjalal Sagor; Randa Mohammed Zaki; Muhammad Fazle Rabbee; Maximilian Lackner (Pharmaceutics)
The demand for developing novel antimicrobial drugs has increased due to the rapid appearance and global spread of antibiotic resistance. Antimicrobial peptides (AMPs) offer distinct advantages over traditional antibiotics, such as broad-range efficacy, a delayed evolution of resistance, and the capacity to enhance human immunity. AMPs are being developed as potential medicines, and current computational and experimental tools aim to facilitate their preclinical and clinical development. Structural and functional constraints as well as a more stringent regulatory framework have impeded clinical translation of AMPs as possible therapeutic agents. Although around four thousand AMPs have been identified so far, there are some limitations of using these AMPs in clinical trials due to their safety in the host and sometimes limitations in the biosynthesis or chemical synthesis of some AMPs. Overcoming these obstacles may help to open a new era of AMPs to combat superbugs without using synthetic antibiotics. This review describes the classification, mechanisms of action and immune modulation, advantages, difficulties, and opportunities of using AMPs against multidrug-resistant pathogens and highlights the need and priorities for creating targeted development strategies that take into account the most cutting-edge tools currently available. It also describes the barriers to using these AMPs in clinical trials.